2020
DOI: 10.1111/bjd.19050
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol mebutate 0·015% gel is safe for short‐term treatment of actinic keratoses on the face in solid organ transplant recipients

Abstract: Propranolol pharmacokinetics in infants treated for infantile hemangiomas requiring systemic therapy: modeling and dosing regimen recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A recent case series in 2020 described the use of ingenol mebutate 0.015% gel for the treatment of AKs on the trunks of 20 organ transplant recipients (9 lung, 11 kidney), and evaluation at the study endpoint of 2 months demonstrated partial clearance of AKs in 60% of patients and complete clearance in 40%, without any significant adverse events or laboratory abnormalities attributed to treatment. 90…”
Section: Ingenol Mebutatementioning
confidence: 99%
“…A recent case series in 2020 described the use of ingenol mebutate 0.015% gel for the treatment of AKs on the trunks of 20 organ transplant recipients (9 lung, 11 kidney), and evaluation at the study endpoint of 2 months demonstrated partial clearance of AKs in 60% of patients and complete clearance in 40%, without any significant adverse events or laboratory abnormalities attributed to treatment. 90…”
Section: Ingenol Mebutatementioning
confidence: 99%